1995
DOI: 10.1103/physrevb.51.2572
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of semiconductor characterization by phonon sidebands in photoluminescence

Abstract: In this paper two GaAs samples were investigated; one was a very pure sample grown by chemicalvapor deposition, the other was grown by molecular-beam epitaxy. The dominant optical transition in the high-purity sample was the donor-bound-exciton transition. Phonon sidebands associated with both the free exciton and the donor-bound exciton were observed. The active phonons were the longitudinaloptical (LO) and the transverse-optical (TO) modes associated with both the free exciton and the donorbound exciton at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Phonon side bands have been observed in optical transitions of many materials. Intrinsic bulk phonon energies as well as impurity-related phonon energies can be determined from the measurements. A phonon side band, however, was not observed from ZnO nanoparticles possibly because of their wide spectra due to nonuniformity of dispersion of the luminescent center. Additionally, the temperature dependence of the band structure decreases by quantization.…”
Section: Resultsmentioning
confidence: 99%
“…Phonon side bands have been observed in optical transitions of many materials. Intrinsic bulk phonon energies as well as impurity-related phonon energies can be determined from the measurements. A phonon side band, however, was not observed from ZnO nanoparticles possibly because of their wide spectra due to nonuniformity of dispersion of the luminescent center. Additionally, the temperature dependence of the band structure decreases by quantization.…”
Section: Resultsmentioning
confidence: 99%
“…Thus the BX band and its LO-phonon replicas can be readily attributed to the recombination of bound excitons as in other materials since the bound excitons should have weaker coupling to the LO phonon. 2,4,8,11 As for the LX band and its LO-phonon replicas, we tentatively ascribe them to the recombination of excitons localized by the interface roughness. One may argue that the two components in the PL spectra could be attributed to the localized excitons and free excitons.…”
mentioning
confidence: 77%
“…For strongly polar semiconductors, longitudinal optical ͑LO͒-phonon replicas of bound and free exciton emission have been observed in both group III-V and group II-VI bulk materials. [1][2][3][4] It has been shown that investigation of LO-phonon replicas provides a useful means to characterize quantum well samples, although experimental results in this aspect are few. [5][6][7] As a wide band gap semiconductor, ZnO has drawn a great deal of attention for application in short wavelength optoelectronic devices.…”
mentioning
confidence: 99%
“…Previously, we have shown in GaAs that the phonons couple much more strongly to the free-exciton transitions than to the bound exciton transitions. 4 We believe that the reason phonon replicas are not generally seen in the PL spectra of direct gap Al x Ga 1Ϫx As alloys is that the bound exciton transitions are dominant over the free-exciton transitions. Assuming the alloy behaves similarly to GaAs the phonon coupling to the bound exciton transitions is considerably weaker than the coupling to the free-exciton transitions.…”
mentioning
confidence: 99%
“…In Ref. 4, a peak in the Raman spectra was observed near 0.0247 eV which was interpreted as the disorder-activated longitudinal acoustic mode. The peaks observed in Fig.…”
mentioning
confidence: 99%